The Effectiveness of PNPM-SPP Program on Society Welfare: Islamic Economic Perspective - Tesa Mellina; Mohammad Ghozali (Jurnal Ilmiah Al-Syir'ah, 2019)
Economic activities in rural areas are still dominated by micro business sectors. The majority of business agents are women who are always constrained by capital in economic activities. Though capital is one of the most important elements in moving the economy in a rural area. Limited capital can prevent creativity in business development. Looking at the facts, people should be able to get capital easily. Program Nasional Pemberdayaan Masyarakat is a national integrated poverty reduction program and is a community empowerment program launched by the government. PNPM in one of its programs facilitates the community in Obtaining additional capital by providing a capital loan for women who have a business, namely Simpan Pinjam Perempuan (SPP) program. This study aims to determine the effectiveness of Simpan Pinjam Perempuan (SPP) program and the Islamic economic perspective of the SPP program in an effort to prosper the Cantuk Banyuwangi community. The variables used to measure the effectiveness of the SPP program are the variables of achieving goals, integration, real change, and satisfaction. Program effectiveness is the dependent variable. The study was conducted on 80 SPP lenders. The selection of respondents was by Sampling Cluster method. As for the data processing, the data was done by quantitative statistical analysis method and used a qualitative descriptive method for analyzing qualitative analysis data. Based on the research, the results showed that the effectiveness of the SPP program in Cantuk Banyuwangi Village was very effective with a percentage of 93.3%.